CONCEPTION RATE BASED ACCURACY OF DIFFERENT METHODS TO DIAGNOSE SUB-CLINICAL ENDOMETRITIS IN COWS - NEELAM (The Indian Journal of Animal Reproduction, 2022)
The status of genitalia (through rectal palpation) and cervico-vaginal discharge at spontaneous estrus was examined in 140 clinically normal cows (Jersey and Jersey crossbred). Endometrial cytology (n=15), bacteriological culture analysis (n=140) and Whiteside test (n=114) used for the diagnosis of sub-clinical endometritis (SCE) in cows recorded the prevalence as 40.0, 58.8 and 55.0%, respectively. With respective methods, the conception rate in SCE positive cows was 40.0, 32.4 and 16.7% and in SCE negative cows was 48.6, 55.6 and 77.8%. Thus, based on conception rate, the endometrial cytology was the most effective test for the diagnosis of SCE.